A Associação Movimentista Escola Sem Partido na cruzada antigênero: análise de sua militância no Instagram - Paolin, Mariana Monti (2022)
In recent decades, given the expansion of human rights involving gender and sexuality in different parts of the world, there has been an effervescence of movements and reactions that have been in opposition, both to the theories of gender developed in the academic field since the 20th century, as well as to to advances in feminist and LGBTQIA+ activism. Aiming at the defense of the "natural family", the anti-gender discourse, recognized by the phrase "gender ideology". In this context, the movement association Escola Sem Partido (ESP) gains centrality in the Brazilian scenario, given its ability to bring together different sectors of civil society around the single agenda of combating “gender ideology”, which its supporters consider a threat to society. family, morality, Christian principles and, consequently, society as a whole. His militancy took place mainly, but not exclusively, in social networks, used as a space for propaganda and dissemination of his principles, values ​​and worldview. Thus, this dissertation aimed to analyze the way in which the anti-gender discourse was appropriated and disseminated by ESP from its posts in the Instagram between 2016 and 2020. For this, a systematic collection and analysis of data from this social network was carried out, focusing on the posted images and interpretation of their captions, using the categorical content analysis method.